Video Design for Clean and Honest Characters Strengthening of Mahasantri Ma'had Al-Jamiah IAIN Padangsidimpuan - ., Magdalena; ., Asnah; Salim Lubis, Agus; Sustri Harida, Eka; Aida Ritonga, Asnil; Tua, Munar (KnE Social Sciences, 2023)
Character Education is an important element in developing affective to be good person especially as mahasantri, and it is significant to create the good value of clean and honest. The study aims to design video of ‘clean and honest living characters’ among mahasantri in Ma’had Al-Jami’ah IAIN Padangsidimpuan. Designing video for ‘clean and honest living character’ is resulted by research and development. This study use Focus Group Discussion as the instrument, beside observation and interview. Based on the instrument, it is found that content of video was designed into two videos of ‘clean character’ and ‘honest character’. These two videos contains of four parts: part 1 is monolog about clean and health life character, part 2 is the slogan of clean and health living character, part 3 is the picture that show the contrast of positive and negative condition, and part 4 is short story about clean and health life character. Keywords: Video design; character education; living characters’